Protein misfolding and clearance in demyelinating peripheral neuropathies: Therapeutic implications - Lee, Samuel M. (Landes Bioscience, 2012)
Peripheral neuropathies such as Charcot-Marie-Tooth disease (CMT) are a group of neurological disorders that affect the peripheral nervous system. Although demyelinating CMT is the most prevalent hereditary peripheral neuropathy, there are currently no effective treatments for patients suffering from this disease. Recent studies by our group and others have provided a link between protein misfolding and demyelinating CMT and indicate that impairment of the proteasome and aggresome-autophagy pathways may contribute to CMT pathogenesis. These studies suggest that targeting protein quality control systems involved in cytoprotection against CMT-associated misfolded proteins could have therapeutic benefits for treating demyelinating CMT.